Altered theta and beta oscillatory synchrony in a genetic mouse model of pathological anxiety. Issue 6 (7th May 2021) - Cruces‐Solis, Hugo; Babaev, Olga; Ali, Heba; Piletti Chatain, Carolina; Mykytiuk, Vasyl; Balekoglu, Nursen; Wenger, Sally; Krueger‐Burg, Dilja
Abstract: While the neural circuits mediating normal, adaptive defensive behaviors have been extensively studied, substantially less is currently known about the network mechanisms by which aberrant, pathological anxiety is encoded in the brain. Here we investigate in mice how deletion of Neuroligin‐2 (Nlgn2), an inhibitory synapse‐specific adhesion protein that has been associated with pathological anxiety and other psychiatric disorders, alters the communication between key brain regions involved in mediating defensive behaviors. To this end, we performed multi‐site simultaneous local field potential (LFP) recordings from the basolateral amygdala (BLA), centromedial amygdala (CeM), bed nucleus of the stria terminalis (BNST), prefrontal cortex (mPFC) and ventral hippocampus (vHPC) in an open field paradigm. We found that LFP power in the vHPC was profoundly increased and was accompanied by an abnormal modulation of the synchrony of theta frequency oscillations particularly in the vHPC‐mPFC‐BLA circuit. Moreover, deletion of Nlgn2 increased beta and gamma frequency synchrony across the network, and this increase was associated with increased center avoidance. Local deletion of Nlgn2 in the vHPC and BLA revealed that they encode distinct aspects of this avoidance phenotype, with vHPC linked to immobility and BLA linked to a reduction in exploratory activity. Together, our data demonstrate that alterations in long‐range functional connectivity link synaptic inhibition to abnormal defensive behaviors, and that both exaggerated activation of normal defensive circuits and recruitment of fundamentally distinct mechanisms contribute to this phenotype. Nlgn2 knockout mice therefore represent a highly relevant model to study the role of inhibitory synaptic transmission in the circuits underlying anxiety disorders.